Adverse Shocks and Economic Insecurity: Evidence from Chile and Mexico - Friedman-Rafael, J; Espinosa-Brito, J; Yevenes-Ortega, C (Blackwell Publishing Ltd, 2014)
This paper uses multinomial logit to analyze economic insecurity for Chile and Mexico from household surveys. It analyzes the effect changes in well-being, age, health, wealth, employment status, gender, and education have on economic insecurity. The results show that the most significant variable is current exposure to adverse events, the second most significant is age, and the third is health. The current exposure to adverse events produces great anxiety and concern about and the inability to recover from these bad events. Older households assign higher probabilities to negative prospects and are thus subject to higher levels of economic insecurity. This also occurs when the household head is seriously ill. The effect of gender and wealth on negative expectations is very small, while education only affects Mexico, and self-employment affects only Chile. Finally, the similarities between Chile and Mexico provide evidence of identifiable patterns for economic insecurity in Latin American countries. © 2013 International Association for Research in Income and Wealth.